Analysis of professional implication as a tool of permanent education in health - Flávio Adriano Borges; Cinira Magali Fortuna; Adriana Barbieri Feliciano; Márcia Niituma Ogata; Maristel Kasper; Mônica Vilchez da Silva
Objective: analyze professional implication with the support of humanization and articulators of permanent education in health as a tool of Permanent Education in Health. Method: this is an interventional study of qualitative approach, based on the theoretical reference of Institutional Analysis. Thirty-five humanization supporters and/or permanent education articulators participated in this study. Semi-structured interviews, monthly meetings, restitution meetings and a daily logbook were used as tools for data production. The material was analyzed according to the principles of the study reference and the results were presented according to the ideological, organizational and libidinal dimensions of professional implication. Results: this study identified a contradiction when finding a professional profile for the development of support and articulation; feelings of discouragement, pessimism and optimism in the development of these roles; influences of the nursing profession on the development of support and articulation; length of professional service; and the absence/presence of desire in such development. Conclusion: the analysis of professional implication consisted of a powerful tool generating training processes. It allowed learning and reflection of the practice through analysis of the actions performed by the professionals, generating changes in the conception of work in health.